2011
DOI: 10.1152/ajplung.00063.2011
|View full text |Cite
|
Sign up to set email alerts
|

The oncogeneTrop2regulates fetal lung cell proliferation

Abstract: The factors regulating growth of the developing lung are poorly understood, although the degree of fetal lung expansion is critical. The oncogene Trop2 (trophoblast antigen 2) is upregulated during accelerated fetal lung growth, and we hypothesized that it may regulate normal fetal lung growth. We investigated Trop2 expression in the fetal and neonatal sheep lung during accelerated and delayed lung growth induced by alterations in fetal lung expansion, as well as in response to glucocorticoids. Trop2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 60 publications
1
23
2
Order By: Relevance
“…We have shown that Trop2 regulates the migration of fetal lung cells [37,58] , which suggests a previously unrecognized role of Trop2 during lung development. In this study, we showed, for the first time, that TROP2 protein is localized in granule cells in all layers of the developing cerebellum, but particularly to the postmitotic, migrating granule cells.…”
Section: The Effect Of Iugr On Molecular Factors That Regulate Granulmentioning
confidence: 76%
“…We have shown that Trop2 regulates the migration of fetal lung cells [37,58] , which suggests a previously unrecognized role of Trop2 during lung development. In this study, we showed, for the first time, that TROP2 protein is localized in granule cells in all layers of the developing cerebellum, but particularly to the postmitotic, migrating granule cells.…”
Section: The Effect Of Iugr On Molecular Factors That Regulate Granulmentioning
confidence: 76%
“…This suggests that Trop2 may play a role in late gestation fetal lung development, which is distinct from that of Epcam . This is supported by the observation that TROP2 is localized to airway and alveolar epithelium, endothelium, smooth muscle cells, and myofibroblasts during normal fetal lung development in rats and sheep (McDougall et al, ). In contrast, EpCAM localization is limited to bronchiolar epithelial cells throughout the embryonic, pseudoglandular, canalicular, and alveolar stages of lung development as well as a subset of alveolar epithelial cells (AECs), likely to be surfactant‐producing type II AECs during the alveolar stage of human lung development (Kasper et al, ).…”
Section: Trop2 In Health and Diseasementioning
confidence: 82%
“…Trop2 expression levels are very high during the canalicular stage in both fetal rats and fetal sheep, when cell proliferation rates are high. However, Trop2 levels increase in fetal rats from the canalicular to the saccular stage of development, but decrease in fetal sheep from the mid‐canalicular through to the alveolar stage of lung development (McDougall et al, ). This may be due to the differences in the development of the lungs and the timing of cellular events in these two species.…”
Section: Trop2 In Health and Diseasementioning
confidence: 99%
See 2 more Smart Citations